Checkpoint inhibitor-induced gastritis followed by delayed severe hepatitis in a patient with lung metastases of head and neck squamous cell carcinoma: a case report - Otsuka, Tomoyuki; Hashii, Yoshiko; Murayama, Sei; Ishizuka, Yasunobu; Kojitani, Yoshiki; Nishio, Minako; Kudo, Toshihiro (Frontiers in Oncology, 2023)
Pembrolizumab, an anti-programmed death-1 (PD-1) receptor monoclonal antibody, is an effective first-line therapy for metastatic head and neck squamous cell carcinoma. Immune-related adverse events (irAEs) are well-described complications of PD-1 inhibitors, and multiorgan irAEs are known to occur occasionally. We report a patient with pulmonary metastases of oropharyngeal squamous cell carcinoma (SCC), who developed gastritis followed by delayed severe hepatitis and recovered with triple immunosuppressant therapy. A 58-year-old Japanese male with pulmonary metastases of oropharyngeal SCC who was treated with pembrolizumab, subsequently developed new-onset appetite loss and upper abdominal pain. Upper gastrointestinal endoscopy revealed gastritis and immunohistochemistry revealed pembrolizumab-induced gastritis. The patient developed delayed severe hepatitis at 15 months after initiating pembrolizumab treatment, presenting “Grade 4 aspartate aminotransferase increase” and “Grade 4 alanine aminotransferase increase.” Impaired liver function persisted despite pulse corticosteroid therapy with intravenous methylprednisolone 1,000 mg/day, followed by oral prednisolone 2 mg/kg/day and oral mycophenolate mofetil 2,000 mg/day. Tacrolimus, which reached target serum trough concentrations of 8–10 ng/mL, gradually improved irAE grades from Grade 4 to Grade 1. The patient responded well to triple immunosuppressant therapy comprising prednisolone, mycophenolate mofetil, and tacrolimus. Therefore, this immunotherapeutic approach could be effective for multiorgan irAEs in patients with cancer.